Driving competitive and facilitative interactions in oak dehesas through management practices - Moreno Marcos, G; Obrador, J J; García, E; Cubera, E; Montero, M J; Pulido, F; Dupraz, C (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.
Keywords: acorn production; forage yield; light; microclimate; root system; soil resources